Jesus, Paul and the law Studies in Mark and Galations - Dunn, James Douglas Grant, 1939- (London, UK SPCK, 1990)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Mark -- criticism, interpretation, etc; Bible. N.T. Galatians -- criticism, interpretation, etc